How effective is corporate governance in preventing financial fraud in Indonesia Kompas100 firms? - Simanullang, Fransiska; Simanullang, Sairun (Privietlab, 2024)
This study examines the relationship between corporate governance practices and the incidence of financial fraud among firms listed on the Kompas100 Index in Indonesia. Utilizing a panel dataset of 1,000 companies over the period from 2015 to 2023, the research employs a Fixed Effects Model (FEM) to analyze the impact of key governance variables, including board composition, ownership structure, and audit committee effectiveness, on fraud occurrence. The findings reveal that firms with a higher proportion of independent directors and more effective audit committees are less likely to engage in financial fraud. Conversely, concentrated ownership and higher leverage are associated with an increased likelihood of fraud. These results underscore the importance of robust governance mechanisms in preventing fraud, particularly in the context of Indonesia's evolving corporate landscape. The study also discusses the limitations of the research and offers policy recommendations to strengthen corporate governance frameworks, thereby enhancing the integrity of Indonesia's financial markets.